WHY IS IT NECESSARY TO DEVELOP PUBLIC RELATIONS IN THE CIVIL SERVICE? - Mansur Yunusov (Galaxy International Interdisciplinary Research Journal, 2022)
In the last period, the most important factors of SMI in the development of links with obshchestvennostyu and formirovanii kommunikatsii s obshchestvennostyu, yavlyayutsya effective use of PR-technologies and effective use of SMI in the creation of the image of the leader, use of information-oriented PR technologies standards.